Bureaucrats Versus Voters: On the Political Economy of Resource Allocation by Direct Democracy - Romer, Thomas; Rosenthal, Howard (Quarterly Journal of Economics, 1979)
I. The setter's problem under certainty and the importance of the reversion point, 565.—II. Budget-maximizing with uncertain turnout, 571.—III. Exploiting a sequence of elections, 579.—IV. Implications for empirical research, 581.—Appendix, 585.